Leak detection characteristics of point and line sensors for foundational data in smart safety management systems - Hyeon-Ki Lee; Tae-Woong Park; Hyeong-Soo Kim; Hyeong-Joo Kim (Sensing and Bio-Sensing Research)
The leak detection characteristics of fifth-generation point sensors and film-type leak sensors were determined to provide foundational data for sensor system research. A comparative analysis of electrical conductivity revealed that sodium hydroxide had approximately 0.5 to 0.6 times the conductivity of sulfuric acid, indicating that alkaline solutions generally have a lower electrical conductivity than acidic solutions. Stable measurements were obtained by setting the minimum measured value to 10 mA. Under this condition, the minimum detectable concentrations were at least 0.2 % for point sensors and at least 0.4 % for line sensors. A 3D graph depicting changes in output values across the entire concentration range for sulfuric acid and sodium hydroxide showed greater variability in measurements for point sensors than line sensors. At high concentrations, the measurements for sulfuric acid were consistently lower than those for sodium hydroxide. The correlation between electrical conductivity and sensor results led to the development of predictive equations. For point sensor measurements, a quartic function was derived based on the concentrations of sulfuric acid and sodium hydroxide solutions, while for line sensor measurements, an exponential function was used. Both measured and predicted values confirmed that the minimum detectable concentrations were at least 0.2 % for point sensors and at least 0.4 % for line sensors. These findings provide valuable data for the development of advanced smart safety management systems.